Ketahanan pangan rumah tangga berhubungan dengan stunting pada anak usia 6-23 bulan - Masrin Masrin; Yhona Paratmanitya; Veriani Aprilia (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2014)
ABSTRACTBackground: Food is one of human basic needs. If it is not fullfilled, both in their number and quality in the individual and household level will disturb the achievement of the life quality that are health, active, and sustainable and able to rise various health and nutrition problems. Stunting in children 6-23 monthswas one of chronical nutrition problems that was caused by access and afford to the food still low.Objectives: To analyze the correlation between food security of the household and stunting incidence in children aged 6-23 months in Sedayu Subdistrict, Bantul, Yogyakarta.Methods: This was an observational study with case-control design. The samples of the study were 126 children aged 6-23 months, each for case, and control group. The samples were chosen by total sampling method. Data were analyzed by using univariate, bivariate, and multivariate. Statistic test in bivariate analysis used chi-square test and in multivariate analysis used logistic regression test.Results: Bivariate analysis showed that food security of the household had correlation with stunting incidence in children aged 6-23 months (p=0.04, OR=2.70, 95% CI:0.94-8.77). The confounding variable which had significant correlation with stunting incidence in children aged 6-23 months were mother height (p=0.00, OR=2.03, 95% CI:1.14-3.65) and low birth weigth history (p=0.03, OR=3.02, 95% CI:0.98-11.04). Multivariate analysis by controlling mother height and low birth weigth history in children aged 6-23 months,showed that household food security had correlation with stunting incidence in children aged their 6-23 months (p=0.05, OR=2.62, 95% CI:0.97-7.12).Conclusions: There was significant correlation between household food security and stunting incidence in children aged at their 6-23 months in Sedayu Subdistrict, Bantul, Yogyakarta.KEYWORDS: household food security, stunting, children aged in 6-23 monthsABSTRAKLatar belakang: Pangan merupakan salah satu kebutuhan dasar manusia. Jika kebutuhan tersebut tidak terpenuhi, baik jumlah maupun mutunya pada tingkat individu dan rumah tangga akan mengganggu tercapainya kualitas hidup sehat, aktif, dan berkesinambungan serta dapat menimbulkan berbagai permasalahankesehatan dan gizi. Baduta stunting merupakan salah satu masalah gizi kronis yang disebabkan oleh akses dan keterjangkauan terhadap pangan masih rendah.Tujuan: Menganalisis hubungan ketahanan pangan rumah tangga dengan kejadian stunting pada balita usia 6-23 bulan di Kecamatan Sedayu, Bantul, Yogyakarta.Metode: Jenis penelitian ini adalah observasional dengan rancangan case-control. Sampel penelitian adalah baduta usia 6-23 bulan yang berjumlah 126 untuk masing-masing kelompok kasus dan kontrol dengan rasio 1:1. Teknik pengambilan sampel menggunakan metode total sampling. Analisis data secarabertahap, yaitu analisis univariat, bivariat, dan multivariat. Uji statistik bivariat menggunakan chi-square dan multivariat menggunakan regresi logistik. Hasil: Hasil analisis bivariat menunjukkan ketahanan pangan rumah tangga berhubungan dengan kejadian stunting pada baduta usia 6-23 bulan (p=0,04, OR=2,70, 95% CI:0,94-8,77). Variabel luar yang berhubungan signifikan dengan kejadian stunting pada baduta usia 6-23 bulan yaitu tinggi badan ibu(p=0,00, OR=2,03, 95% CI:1,14-3,65) dan riwayat BBLR (p=0,03, OR=3,02, 95% CI:0,98-11,04). Hasil analisis multivariat dengan mengendalikan variabel tinggi badan ibu dan riwayat BBLR baduta menunjukkan ketahanan pangan rumah tangga berhubungan dengan kejadian stunting pada baduta usia 6-23 bulan (p=0,05, OR=2,62, 95% CI:0,97-7,12).Kesimpulan: Ada hubungan yang signifikan antara ketahanan pangan rumah tangga dengan kejadian stunting pada baduta usia 6-23 bulan di Kecamatan Sedayu, Bantul, Yogyakarta.KATA KUNCI: ketahanan pangan rumah tangga, stunting, baduta usia 6-23 bulan